CREDIT SALES ACCOUNTING INFORMATION SYSTEM AS A MEANS OF CONTROLLING RECEIVABLES IN DRUG COMPANIES - Sariyanto Renny (Jurnal Ekonomi, 2022)
The Covid-19 pandemic has affected various aspects of life including the marketing aspect of medicines. There are many requests related to medicines from hospitals, especially referral hospitals handling covid-19. The demand for such medicines must be met immediately given the urgency of the need, but in the realization of payment of orders for such products can be done with a credit sales system, so the realization of payments sometimes experiences obstacles. Pt. Sapta Sari Tama, which is engaged in medicines, already has an accounting information system, but it is seen that the company is still experiencing problems in collecting receivables. This is because the company has never conducted an evaluation of the application and effectiveness of the accounting information system they use. Therefore, a study is needed to analyze the application and effectiveness of the accounting information system used by PT. Sapta Sari Tama (feasibility study). The problem studied is how to apply and effectively the credit sales accounting information system in PT. Sapta Sari Tama. The specific purpose of this study is to analyze the application and effectiveness of the credit sales accounting information system, so that it can be used as input to the company in making a strategy for controlling the collection of receivables. This research method is the research approach used in this study is a descriptive quantitative approach, where this research focuses on deciphering and identifying problems about the credit sales accounting information system to support the internal control of PT. Sapta Sari Tama Medan. This research consists of 2 stages, namely Analysis of the Application of the Accounting Information System (SIA) for Credit Sales and Analysis of the effectiveness of SIA. Credit sales system at PT. Sapta Sari Tama Medan Branch Includes Sales Function, Accounting Function, Warehouse Function, Delivery Function. And the documents used are Purchase Order Letters (SOPs), Invoices and RECAPITULATION OF COGS. The records used are the Sales journal and the Inventory card